2012
DOI: 10.1007/s00774-012-0372-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of risedronate (17.5 mg/week) treatment on quality of life in Japanese women with osteoporosis: a prospective observational study

Abstract: A prospective observational study to test the effects of risedronate 17.5 mg/week treatment on quality of life (QOL) of 1,363 Japanese female patients with osteoporosis showed QOL improvement after 12 weeks of administration. Comorbid factors such as ischemic heart disease, hip osteoarthritis, and higher values of FRAX blunted the effects of QOL of the treatment. Few studies have investigated the effect of osteoporosis treatment on QOL in relationship to comorbid factors other than osteoporosis and fracture. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In another 12‐week long observational study (17.5 mg/week risedronate) with 1363 Japanese females, the greatest improvement concerned the dimension of ‘pain/discomfort’ in QOL (Nakamura et al, 2012). In a 3‐year post‐marketing study of once monthly 75 mg risedronate in 285 patients with low back pain (presence/absence, but not evaluated by VAS or QOL), the proportion of patients with low back pain decreased gradually by 30.77% at 36 months (Soen et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In another 12‐week long observational study (17.5 mg/week risedronate) with 1363 Japanese females, the greatest improvement concerned the dimension of ‘pain/discomfort’ in QOL (Nakamura et al, 2012). In a 3‐year post‐marketing study of once monthly 75 mg risedronate in 285 patients with low back pain (presence/absence, but not evaluated by VAS or QOL), the proportion of patients with low back pain decreased gradually by 30.77% at 36 months (Soen et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported on the increase t EQ‐5D utility score after initiation of osteoporosis treatment . Nakamura et al reported that a weekly dose of risedronate improved the EQ‐5D score in Japanese women with osteoporosis. Langdahl et al reported that the improvement in the EQ‐5D score with teriparatide treatment specifically resulted from a decrease in back pain.…”
Section: Discussionmentioning
confidence: 99%